Optical flux behaviour of a sample of Fermi blazars - Marchesini, Ezequiel Joaquín (2016)
Aims. We aim at investigating the time-behaviour of a sample of gamma-ray blazars. We present the results from a 13 month-long optical photometry monitoring campaign of the blazars PKS 0048-097, PKS 0754+100, [HB89] 0827+243, PKS 0851+202, PKS 1253-055, PKS 1510-089, PKS 1749+096, PKS 2230+114 and PKS 2251+158. Methods. We analyse the variability of each object, focusing on different time-scales (long term, short term, and microvariability), in an attempt to achieve a statistical comparison of the results. Results. After applying a geometric model to explain the variability results, we found that it is possible that a slight change in the direction of the jet generates the variations detected in some objects during this campaign.